Ernest Hemingway the life and the legend - Lyttle, Richard B. (Atheneum Maxwell Macmillan Canada Maxwell Macmillan International, 1992)
Studies the life and works of the twentieth century American author, describing the childhood and adult experiences that became common themes in many of his stories and novels.